Granger Causality Test of Net Interest Margin and Liquidity - Sari, Pristin Prima; Putra, Ardian Prima; Rinofah, Risal (Jurnal Analisis Bisnis Ekonomi, 2020)
The study aims to compute causality Granger test on Net Interest Margin (NIM) and liquidity Bank Listed in Indonesia Stock Exchange for the period 2014-2018. Variable of liquidity uses proxies Legal Reserve Requirement (LRR) and Loan to Deposit Ratio (LDR). The statistics tool is E-Views 8th with Granger Causality test. The Data research is financial statement Bank in IDX. We provide finding in the relationship among NIM, LRR and liquidity ratio Bank. We found result that there is Granger causality NIM and LRR, NIM and Loan to Deposit Ratio (liquidity) and Reserve Requirement and LDR. The study is beneficial for management bank to make policy in net interest margin and liquidity, for future research to develop empirical literature in net interest margin, Legal Reserve Requirement and Loan to Deposit Ratio.